Cloning and Characterization of a New Chitosanase From a Deep-Sea Bacterium Serratia sp. QD07 - Zheng, Qiuling; Meng, Xiangjun; Cheng, Mingyang; Li, Yanfeng; Liu, Yuanpeng; Chen, Xuehong (Frontiers in Microbiology, 2021)
Chitosanase is an important chitosan-degrading enzyme involved in industrial applications, which forms chitooligosaccharides (COS) as reaction products that are known to have various biological activities. In this study, a new chitosanase encoding gene, csnS, was cloned from a deep-sea bacterium Serratia sp. QD07 and over-expressed in Escherichia coli. Cell culture of the recombinant strain was carried out in a 5 L fermenter, which yielded 324 U/mL chitosanases. The purified CsnS is a cold-adapted enzyme, which showed highest activity at 60 °C, and exhibited 37.5% and 42.6% of its maximal activity at 0 °C and 10 °C, respectively. It exhibited optimum activity at pH 5.8 and was stable at a pH range of 3.46-8.88. Additionally, CsnS exhibited an endo-type cleavage pattern and hydrolyzed chitosan polymers to yield disaccharides and trisaccharides as the major reaction products. These results make CsnS a potential candidate for the industrial manufacture of COS.